Significance of the Nanograin Size on the H2S-Sensing Ability of CuO-SnO2 Composite Nanofibers. (24th February 2015) - Katoch, Akash; Kim, Jae-Hun; Kim, Sang Sub
Abstract : CuO-SnO2 composite nanofibers with various nanograin sizes were synthesized for investigating their sensing properties with respect to H2 S gas. The nanograin size in the CuO-SnO2 composite nanofibers was controlled by changing the thermal treatment duration under isothermal conditions. The nanograin size was found to be critical for the sensing ability of the composite nanofibers. The CuO-SnO2 composite nanofibers comprised of small-sized nanograins were more sensitive to H2 S than those with larger-sized nanograins. The superior sensing properties of the CuO-SnO2 composite nanofibers with the smaller nanograins were attributed to the formation of the larger number of p -CuO- n -SnO2 junctions and their transformation to metallic -CuS- n -SnO2 contacts upon exposure to H2 S gas. The results suggest that smaller nanograins are conducive to obtaining superior H2 S-sensing properties in CuO-SnO2 composite nanofibers.